2017
DOI: 10.1530/erc-17-0040
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for the occurrence of sporadic pancreatic endocrine neoplasms

Abstract: Pancreatic neuroendocrine neoplasms (PNENs) represent 10% of all pancreatic tumors by prevalence. Their incidence has reportedly increased over recent decades in parallel with that of pancreatic adenocarcinoma. PNENs are relatively rare, and of the few institutions that have published potential risk factors, findings have been heterogeneous. Our objective was to investigate the association between potential risk and protective factors for the occurrence of sporadic PNENs across a European population from sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…Furthermore, the BMI was significantly higher in patients with NET vs. PDAC (29% vs. 11%, p=0.043). This is similar to the results of a meta-analysis [46], although contradictory findings exist [47]. However, we found no association of obesity with survival in PC, contrary to other studies that showed that obesity is associated with poorer survival [43,44,48].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the BMI was significantly higher in patients with NET vs. PDAC (29% vs. 11%, p=0.043). This is similar to the results of a meta-analysis [46], although contradictory findings exist [47]. However, we found no association of obesity with survival in PC, contrary to other studies that showed that obesity is associated with poorer survival [43,44,48].…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, most studies that were aimed at unravelling the biology of GEP-NETs focused primarily on tumor genetics or molecular pathways underlying intrinsic pathological features [3,26,27], while the potential contribution of environmental factors was mostly neglected. Indeed, only a small number of retrospective studies have addressed the potential relationship between obesity, MetS, or T2DM and GEP-NETs [26,28,29], and the rare studies available were predominantly dedicated to pNETs only [30,31]. In 2016, the largest subset meta-analysis ever performed disclosed BMI and T2DM, in addition to family history of cancer, as unpredicted risk factors for stomach, pancreas, and small-intestine GEP-NETs [32].…”
Section: Discussionmentioning
confidence: 99%
“…Increased prevalence of impaired glucose tolerance in patients with serotonin secreting metastatic NETs when compared to non-secreting tumors was initially reported in 1975 [ 30 ]. Moreover, a recent publication from Valente et al concluded that non-recent diabetes was associated with an increased occurrence of pNETs especially in metastatic disease and an advanced grade [ 31 ].…”
Section: Discussionmentioning
confidence: 99%